Bidirectional relationships between cigarette use and spinal pain in adolescents accounting for psychosocial functioning - Gill, D.; Davis, Melissa; Smith, Anne; Straker, Leon (John Wiley & Sons Ltd., 2014)
Objectives: The objective of this study was to determine the presence of possible bidirectional causal pathways between cigarette use and spinal pain in adolescents controlling for psychosocial functioning, using a prospective longitudinal research design. Design: The data for this study was collected from a cohort of Australian adolescents at 14 (n = 1596) and 17 (n = 1291) years of age. Methods: Multivariable logistic regression was used to assess i) if cigarette use at 14 predicted low back pain (LBP), mid back pain (MBP) or neck shoulder pain (NSP) at 17 in those adolescents without each condition at 14, and ii) if back pain only (BP), neck shoulder pain only (NSP) or comorbid BP and NSP at 14 predicted cigarette use at 17 in those adolescents who did not smoke at 14.Results. After controlling for psychosocial factors, cigarette use at 14 predicted MBP at 17 (OR = 3.05, p = 0.049, 95% CI [1.01-9.24]). BP only at 14 was a significant risk factor for smoking at 17 (OR = 1.84, p = 0.006, 95% CI [1.19-2.84]) after controlling for psychosocial factors. Conclusion: The findings indicate that there are bi-directional relationships between cigarette use and spinal pain and that these relationships vary with pain location.